AB1119 A descriptive study of gout patients in a multi-ethnic society. (15th June 2017) - Chua, C; Cheung, P; Santosa, A; Lim, A; Teng, GG
Abstract : Background: Gout is a common inflammatory arthritis with rising global prevalence and health burden, especially in the Asia-pacific regions. Ethnicity may play a significant role suggesting lifestyle and/or genetic predisposition, but studies in Asia are limited 1, 2 . Objectives: Our study sought to assess the demographic and clinical factors of gout in the multi-ethnic Singapore and describe the burden and treatment pattern in our patients. Methods: 282 adults with rheumatologist-diagnosed gout were recruited from rheumatology clinics of an academic medical centre in Singapore. Data on demographic and lifestyle features, medical conditions, gout severity and treatment were obtained. Results: 282 subjects were recruited and 92.6% were men. There were 77% Chinese, 18.8% Malays and 2.5% Indians, compared to Singapore's population makeup (74%, 13% and 9% respectively). Mean age at recruitment was 52.6 years (SD 16.1) while age at gout onset was 42.5 years (SD 16.7). 34.4% received primary or no education; 67.0% were employed and 20.7% retired. 22.7% were current alcohol drinkers while 50.7% were teetotalers. 23.4% were current smokers. Mean body mass index (BMI) was 28.1kg/m 2 (SD 6.0), 26.6% had BMI ≥30kg/m 2 while 69.9% had BMI ≥25kg/m 2 . Prevalence of hypertension was 56.7%, diabetes mellitus 18.8%, dyslipidemia 48.2% and chronic kidney disease (CKD, defined as glomerular filtration rate <60ml/min/1.73m 2 ) 32.4%. Malays had significantly less alcohol intake (1.9%) but higher proportions of diabetes (32.1%), CKD (50.9%) and obesity (54.7%), compared with Chinese subjects (26.3%, 16.1%, 28.6% and 19.8% respectively, all Ps <0.05). Gout severity was rated moderate by 30.9% and severe in 50.4%; 69.3% suffered ≥3 attacks in 6 months. Mean SU was 477.8μmol/L (SD 130.8). 80.1% were on allopurinol. Subjects (22.3%) who achieved serum urate (SU) ≤360μmol/L, when compared to those with SU >360μmol/L, were more likely to be on urate lowering therapy (82.5% vs 60.7%, P=0.001), on higher mean allopurinol dose [337 mg/d (SD 166) vs 233 mg/d (SD 140), P<0.001] and statin (54.8% vs 33.3%, P=0.003). There were no significant differences amongst ethnicities for SU levels, gout severity and number of attacks. Conclusions: Gout has substantial health burden in Singapore. Hypertension, dyslipidemia and obesity are more prevalent in our gout subjects compared to our population. Despite notably less alcohol intake compared with other cohorts 3–5, Singapore Malays seemed to suffer higher prevalence and comorbidities of gout. Majority of patients had moderate to severe disease but less than 25% achieved target SU levels highlighting suboptimal management of gout locally. References: Kuo CF, et al. Global epidemiology of gout: prevalence, incidence and risk factors. Nat Rev Rheumatol 2015;11(11):649–62. Krishnan E, et al. Gout in ambulatory care settings in the United States. J Rheumatol 2008;35(3):498–501. Lee CH, et al. Factors associated with gout in South Koreans: analysis using the National Health Insurance Corporation and the National Health Screening Exam databases. Clin Rheumatol 2013;32(6):829–37. Cea Soriano L, et al. Contemporary epidemiology of gout in the UK general population. Arthritis Res Ther 2011;13(2):R39. Vázquez-Mellado J, et al. Metabolic Syndrome and Ischemic Heart Disease in Gout. J Clin Rheumatol 2004;10(3):105–09. Disclosure of Interest: None declared